Traumatic Brain Injury Leads to Development of Parkinson's Disease Related Pathology in Mice - Impellizzeri, Daniela; Campolo, Michela; Bruschetta, Giuseppe; Crupi, Rosalia; Cordaro, Marika; Paterniti, Irene; Cuzzocrea, Salvatore; Esposito, Emanuela (Frontiers in Neuroscience, 2016)
Traumatic brain injury (TBI) is a major health and socio-economic problem that affects all societies. This condition results from the application of external physical strength to the brain that leads to transitory or permanent structural and functional impairments. Moreover, TBI is a risk factor for neurodegeneration and can e.g. increase the risk for Parkinson’s disease (PD), a late-onset neurodegenerative disorder with loss of dopaminergic neurons in substantia nigra. In this study, we wanted to explore the possible development of PD-related pathology within the context of an experimental model of TBI. Traumatic brain injury was induced in mice by controlled cortical impact. At different time points behavioral tests (open field, elevated plus maze tests and Barnes maze) were performed: The animals were sacrificed 30 days after the impact and the brains were processed for Western blot and immunohistochemical analyses. Following TBI there was a significant decrease in expression of tyrosine hydroxylase and dopamine transporter in the substantia nigra as well as significant behavioral alterations. In addition, a strong increase in neuroinflammation was evident, as shown by increased levels of cyclooxygenase-2 and inducible nitric oxide synthase as well as IκB-α degradation and nuclear-κB translocation. Moreover, neurotrophic factors such as brain-derived neurotrophic factor, neurotrophin-3, nerve growth factor, and glial cell line-derived neurotrophic factor were decreased 30 days post-TBI. Interestingly, we observed a significant accumulation of α-synuclein in microglia compared to astrocytes. This study suggests that PD-related molecular events can be triggered upon TBI. The biological mechanisms linking brain trauma and neurodegenerative diseases need to be further investigated.